Comparison of photovoltaic nanogrid implementation: a simple reliability model for frontier, remote, and disadvantaged areas - Ryandi Ryandi; Kevin Marojahan Banjar-Nahor; Nanang Hariyanto (Bulletin of Electrical Engineering and Informatics, 2022)
This paper aims to evaluate the photovoltaic (PV) nanogrid implementation and its risk for a project at a remote location. Unlike the normal approach, this approach is based on a discontinuity project. The main advantage of the model is the simplicity to compute the expected lifetime and display the reliability curve. The reliability is calculated using state space equation and a quantitative approach evaluates the risk of PV nanogrid scenarios based on costs. The MATLAB/Simulink simulates the scenarios including the basic scenario of a PV system that is a PV nanogrid consisting of a PV array and inverter, scenario 1 that is a PV nanogrid with a battery system, scenario 2 is an extension of scenario 1 with a battery repair, and scenario 3 is a PV nanogrid connected to the grid. The result indicates that adding a battery system increases the reliability and the expected lifetime of the system, and the battery system’s maintenance makes it higher. Scenario 3 shows high reliability and a longer expected lifetime. The risk matrix shows the position of reliability and its impact on each scenario. This work can be used in practice as an objective assessment to electrify frontier, remote, and disadvantaged (3T) areas beside levelized cost of energy (LCOE).